2019
DOI: 10.2135/cropsci2018.12.0753
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cover Crops on Weed Suppression, Wheat Yield, and Water Conservation in Winter Wheat–Sorghum–Fallow

Abstract: Reducing the fallow period by using cover crops in a winter wheat (Triticum aestivum L.)–sorghum [Sorghum bicolor (L.) Moench]–fallow system has the potential to suppress weeds and improve wheat yield, yet limited information is available from the semiarid southern Great Plains (SGP) of the United States. This study determines the effects of spring‐planted cover crops on weed suppression and winter wheat yields in semiarid environments. The study used a randomized complete block design with eight cover crop tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 60 publications
3
19
1
Order By: Relevance
“…Mesbah et al. (2019) from the same experiment reported that cover crop biomass returned to the soil in 2017 was greater with oat (2,873 kg ha −1 ), POmix (3,077 kg ha −1 ), POCmix (2,816 kg ha −1 ), and SSmix (2,482 kg ha −1 ) than pea (1,445 kg ha −1 ) and canola (1,847 kg ha −1 ). Pea matures early and uses less soil water than cereals leaving more soil water available for the following crops or fallow period (Lenssen, Johnson, & Carlson, 2007), which may stimulate microbial activity and greater CO 2 –C fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…Mesbah et al. (2019) from the same experiment reported that cover crop biomass returned to the soil in 2017 was greater with oat (2,873 kg ha −1 ), POmix (3,077 kg ha −1 ), POCmix (2,816 kg ha −1 ), and SSmix (2,482 kg ha −1 ) than pea (1,445 kg ha −1 ) and canola (1,847 kg ha −1 ). Pea matures early and uses less soil water than cereals leaving more soil water available for the following crops or fallow period (Lenssen, Johnson, & Carlson, 2007), which may stimulate microbial activity and greater CO 2 –C fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…We included the cost of only one application of the herbicide in the fallow plot during the cover crop growing period. Mesbah et al (2019) demonstrate weed suppression with cover cropping, which can reduce 1-2 more sprays during summer and change the relative effects of cover crops. Finally, the analytical framework used in this study has its own set of limitations, including the concavity of utility function and risk bounds that requires caution in generalizing the results.…”
Section: Discussionmentioning
confidence: 96%
“…Studies at the same experimental location revealed that cover crops have increased soil biological activity, improved soil organic matter accumulation, and suppressed weeds [44,47]. We did not analyze the potential long-term economic benefits of these aspects.…”
Section: Secondary Benefits Subsidy and The Role Of Agricultural Rementioning
confidence: 99%
“…Weed suppression can be achieved by CC due to several reasons including the amount of CC biomass produced (Hodgdon, Warren, Smith, & Sideman, 2016; Mesbah, Nilahyane, Ghimire, Beck, & Ghimire, 2019), decreased light availability resulting from canopy coverage of CC (Masilionyte et al., 2017; Teasdale & Mohler, 2000), allelopathic inhibition of weed germination (Mwaja, Masiunas, & Weston, 1995; Reiss, Fomsgaard, Mathiassen, & Kudsk, 2018), and competition for water and nutrients (Blanco‐Canqui et al., 2015). One of the major factors that dictates weed control is biomass production of CC.…”
Section: Introductionmentioning
confidence: 99%